Rate of Unexpected Findings in Adolescent Lumbar Magnetic Resonance Imagings Ordered by Orthopaedic Surgeons - Bilal S. Siddiq, BS; Anna Rambo, MD; Benjamin Sheffer, MD; Vania Ejiofor, BA; Abu M. Naser, PhD; Trevor McGee, MD; William C. Warner, Jr., MD; Derek M. Kelly, MD (Journal of the Pediatric Orthopaedic Society of North America)
Background: The use of advanced imaging in children is increasing and unexpected findings (UFs) are often detected. The present literature lacks studies investigating the rate of UFs in pediatric lumbar spine magnetic resonance imagings (MRIs) and the sequelae of these findings. This study aimed to determine the overall incidence of UFs in adolescent lumbar MRIs, characterize these findings, stratify UFs based on patient characteristics, and determine any influences on patient treatment plans. Methods: Medical records of 1409 patients aged 10 to 18.5 years old that had a lumbar MRI ordered by an orthopaedic surgeon from 2010 to 2020 were reviewed retrospectively. Demographics, insurance, reason for MRI, and change in treatment plans were noted. Unexpected findings were characterized as spinal cord, infra-peritoneal, retroperitoneal, peritoneal, or vascular-related. The relationship between patient characteristics and UFs was investigated using a t test and Chi-square test. The statistical relationships between UFs and treatment plan changes were evaluated using generalized linear models with a log link and a binomial error distribution. Results: The average age of the 1409 patients was 15.5 years (95% CI: 15.4, 15.6). Back pain (90.1%) was the most common reason for lumbar MRI. Thirty-five UFs were found in 33 patients (2.3%): 19 were spinal cord-related, 15 were peritoneal-related, and one was vascular. Eight peritoneal findings involved the kidneys: two atrophy, two hypoplasia, two renal cysts, one pelvic kidney, and one hydronephrosis. Five patients had a syrinx, and two had spine tumors. Out of 33 patients with UFs, 11 required a change in treatment plan (33.3%). Back pain was not associated with an increased risk of UF. Patients with an UF on MRI had 2.60 times higher odds of experiencing a change in treatment plan. Conclusions: The prevalence of UFs was 2.5% on lumbar MRIs and were mainly spinal cord or retroperitoneal-related. UFs were associated with an altered treatment plan 33% of the time and were unrelated to standard demographic characteristics or insurance type. Key Concepts: (1) Overall, 33.3% of patients with an unexpected finding had a change in treatment plan. (2) Unexpected findings should be interpreted in the context of the patient’s overall clinical picture, symptoms, and health to help elucidate the next steps in treatment. (3) The clinical significance of unexpected findings needs to be further studied. Level of Evidence: Level III, Retrospective